Pengembangan Buku Panduan Konseling Kognitif Behavioral Teknik Cognitive Restructuring Untuk Meningkatkan Kebahagiaan Siswa SMP - Ni Putu Ariasih Ni Putu Ariasih; Kadek Suranata Kadek Suranata; I Ketut Gading I Ketut Gading (SCHOULID: Indonesian Journal of School Counseling, 2023)
This research was carried out with the aim of developing, testing feasibility and effectiveness of a cognitive behavioral techniques counseling manual Cognitive restructuring to increase junior high school students' happiness. This research is research and development (research & development) with using 4D models. Data collection in this validity test was carried out by using the expert validity instrument described by used the CVR and CVI formulas and effectiveness tests in this research involving 31 students of class IX A11 at SMP Negeri 1 Singaraja as subjects research, using one group pre-test and post-test experiments design explained using the t test. The research results show very suitable category. It can be concluded that the use of guidebooks cognitive behavioral counseling effective cognitive restructuring techniques for increasing the happiness of middle school students.